EDUKASI PENDIDIKAN KESEHATAN REPRODUKSI (KESPRO) REMAJA PADA KADER POSYANDU REMAJA LEMBAGA PEMBINAAN KHUSUS KELAS I MEDAN - Bancin, Dewi; Sitorus, Friska; Anita*, Surya (Universitas Sari Mutiara Indonesia, 2022)
The definition of adolescents according to WHO is the population in the age range of 10-19 years, while according to the Regulation of the Minister of Health of the Republic of Indonesia Number 25 of 2014 adolescents are residents in the age range of 10-18 years. The Population and Family Planning Agency (BKKBN) has its own definition of youth, according to the BKKBN, adolescents are defined as residents in the age range 10-24 and unmarried (Infodatin Ministry of Health RI, 2014). Health education is one of the methods used to increase a person's knowledge and abilities through practical learning techniques or instructions with the aim of changing or influencing human behavior individually, in groups, or in society to be more independent in achieving the goals of healthy living. The role of the material provider in this counseling is to deliver material related to adolescent reproductive health and the practice of preventing premenstrual complaints (Maryam, 2015). Based on the initial survey conducted at the Medan Class 1 Special Development Institute, data on the number of occupants were 115 people with various types of problems 39% theft, 11% drugs, 7% sexual abuse and 43% child protection, and after being interviewed with 5 teenagers in private apparently they never knew about reproductive health